Optimization of Establishment, Protoplast Separation, and Fusion via Embryonic Suspension System in Chestnut (Castanea mollissima Bl.) - Shiying Zhang; Sujuan Guo; Ruijie Zheng (Agronomy)
Castanea mollissima Bl. is rich in nutrition and strong in stress resistance, and has nutritional, economic, and ecological values. A protoplast is impactful in somatic fusion and germplasm creation. Here, we propose an effective scheme for the construction of an embryonic suspension cell, protoplast isolation, and fusion. Studies have shown that when 1.0 g yellow loose embryonic callus was inoculated into MS + 1.5 mg∙L−1 6-BA + 0.2 mg∙L−1 NAA + 0.5 mg∙L−1 2, 4-D liquid medium, a stable suspension cell line can be obtained. After further culturing for 2–4 days, protoplast isolation was performed. First, single-factor screening was conducted on the four enzymes, and then a two-factor random block was further set up to screen the enzyme combinations based on the results. We found that 1.0%cellulase R-10 + 0.5%pectolase Y-23 led to the highest protoplast yield (9.27 × 106/g FW) and the highest activity (92.49%). Furthermore, the protoplast yield could be increased to 9.47 × 106/g FW by adding 0.4 M mannitol and shaking for 8 h. The protoplasts were purified by centrifuging at 40× g for 4 min and then mixed with 30% PEG 6000 at a volume ratio of 1.5:1 for 25 min. The fusion rate could reach 70.00%. This study laid a foundation for the creation of new germplasm by Castanea mollissima Bl.